Effects of different half‐time strategies on second half soccer‐specific speed, power and dynamic strength. Issue 1 (3rd August 2011) - Lovell, R.; Midgley, A.; Barrett, S.; Carter, D.; Small, K.
<x xml:space="preserve">Abstract</x> This study compared the effects of whole body vibration (WBV) and a field‐based re‐warm‐up during half‐time (HT) on subsequent physical performance measures during a simulated soccer game. Ten semi‐professional male soccer players performed 90‐min fixed‐intensity soccer simulations (SAFT90), using a multi‐directional course. During the HT period players either remained seated (CON), or performed intermittent agility exercise (IAE), or WBV. At regular intervals during SAFT90, vastus lateralis temperature (Tm) was recorded, and players also performed maximal counter‐movement jumps (CMJ), 10‐m sprints, and knee flexion and extension contractions. At the start of the second half, sprint and CMJ performance and eccentric hamstring peak torque were significantly reduced compared with the end of the first half in CON (P≤0.05). There was no significant change in these parameters over the HT period in the WBV and IAE interventions (P>0.05). The decrease in Tm over the HT period was significantly greater for CON and WBV compared with IAE (P≤0.01). A passive HT interval reduced sprint, jump and dynamic strength performance. Alternatively, IAE and WBV at HT attenuated these performance decrements, with limited performance differences between interventions.